New developments in transnational education and the challenges for higher education professional staff. (2nd January 2017) - Henderson, Michelle; Barnett, Rebecca; Barrett, Heather
Abstract : Transnational education (TNE) is a fast moving area. The growth of TNE provision across the higher education (HE) sector has meant professional staff have developed considerable experience and knowledge in this field. However, the development of online and distance learning provision combined with the changing TNE landscape has given rise to new and innovative partnership types and models, creating new market opportunities, and inevitably more competition. New market entrants offer customised content, routes to qualifications, learning and tuition solutions, which present new partnership opportunities for universities. However, organisational practices for due diligence, stakeholder management, quality assurance, financial investment, decision-making and commercial and legal support can require significant adaptation and management. Professional staff must consider new ways to evaluate potential opportunities and risks in TNE where these involve multiple agencies and third parties. This article provides an insight into how these changes in the TNE environment impact professional staff in HE.